KRAS mutation‐independent downregulation of MAPK/PI3K signaling in colorectal cancer. Issue 5 (1st January 2022) - Lam, Kuen Kuen; Tang, Choong Leong; Tan, Emile; Wong, Siew Heng; Cheah, Peh Yean
Abstract : KRAS is a gatekeeper gene in human colorectal tumorigenesis. KRAS is 'undruggable'; hence, efforts have been diverted to inhibit downstream RAF/MEK/ERK and PI3K/Akt signaling. Nevertheless, none of these inhibitors has progressed to clinical use despite extensive trials. We examined levels of phospho‐ERK1/2(T202/Y204) and phospho‐Akt1/2/3(S473) in human colorectal tumor compared to matched mucosa with semi‐quantitative near‐infrared western blot and confocal fluorescence immunohistochemistry imaging. Surprisingly, 75.5% (25/33) of tumors had lower or equivalent phospho‐ERK1/2 and 96.9% (31/32) of tumors had lower phospho‐Akt1/2/3 compared to matched mucosa, irrespective of KRAS mutation status. In contrast, we discovered KRAS ‐dependent SOX9 upregulation in 28 of the 31 (90.3%) tumors. These observations were substantiated by analysis of the public domain transcriptomics The Cancer Genome Atlas (TCGA) and NCBI Gene Expression Omnibus (GEO) datasets and proteomics Clinical Proteomic Tumor Analysis Consortium (CPTAC) dataset. These data suggest that RAF/MEK/ERK and PI3K/Akt signaling are unlikely to be activated in most human colorectal cancer. Abstract : Phospho‐ERK1/2 and phospho‐Akt1/2/3 are downstream effectors of KRAS signaling frequently used as endpoints for drug testing. We showed that phospho‐ERK1/2 and phospho‐Akt1/2/3 are not upregulated in colorectal cancer (CRC) tumors compared to matched mucosa, regardless of KRAS mutation status. Instead, SOX9 is upregulated in a KRAS ‐dependent manner and thus may be a more suitable effector of KRAS signaling in CRC.